MIRERC 055/2025: LONGITUDINAL STUDY OF PERSISTENT HIGH-RISK HUMAN PAPILLOMAVIRUS INFECTION IN WOMEN LIVING WITH HIV IN MERU, KENYA - Onyambu, Dr. Frank; Celestine Kemunto; Sharon Nyagaka (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Background: Cervical cancer remains the leading cause of cancer-related deaths among women in Kenya, with high-risk human papillomavirus (hrHPV) as the primary etiological agent. Women living with HIV (WLHIV) are disproportionately affected due to immunosuppression. The interactions between hrHPV persistence, sexually transmitted infections (STIs), cytokine imbalances, and vaginal microbiome disruptions is not fully understood in this population. Objective: This study aims to investigate the determinants of persistent hrHPV infection among WLHIV in Meru County, Kenya, focusing on STI co-infections, cytokine profiles, vaginal microbiome structure, and sexual behavior patterns over a five-year period. Methods: We will recruit 500 WLHIV, including 242 from a prior cohort. Annual clinical exams, vaginal swabs, and blood samples will be collected. Data will be collected on behavioral characteristics and other risk factors associated with STIs and HPV infection. HPV and STI screening will be performed using GeneProof PCR kits, cytokines measured via ELISA, and vaginal microbiomes profiled using 16S rRNA sequencing on Illumina MiSeq. Statistical analyses will be conducted in R 4.4.1, using logistic regression and longitudinal mixed models. Expected Outcomes: The study will generate data that will improve understanding of how into microbial, immunological, and behavioral factors influencing hrHPV persistence. This will inform new prevention strategies such as vaginal probiotics, immune-targeted therapies, and public health interventions tailored to WLHIV.